Low leptin levels predict amenorrhea in underweight and eating disordered females - Köpp, Werner; Blum, W. F.; von Prittwitz, S.; Ziegler, A.; Lübbert, H.; Emons, G.; Herzog, Wolfgang; Herpertz, S.; Deter, H.-C.; Remschmidt, H.; Hebebrand, Johannes (Molecular psychiatry, 1997)
Evidence that leptin plays an important role in reproductive function is accumulating rapidly. We hypothesized that low leptin synthesis is associated with amenorrhea. We therefore determined serum leptin levels in 43 underweight female students, who were screened for lifetime occurrence of amenorrhea. We assessed the predictive value of leptin, body mass index (BMI), fat mass and percent body fat, respectively, for lifetime occurrence of amenorrhea. Factors predicting amenorrhea were tested for their capability to predict current amenorrhea in a second cohort of 63 inpatients with anorexia nervosa (AN) or bulimia nervosa (BN). Furthermore, the relationships between serum leptin levels and of follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol and progesterone, respectively, were evaluated. Only leptin predicted lifetime occurrence of amenorrhea in the student cohort. The critical leptin level was in the range of 1.85 μg L−1. This level served to largely separate anorectic from bulimic patients. In patients with AN mean serum log10 leptin levels over the first 4 weeks of inpatient treatment were correlated with mean FSH, LH and estradiol levels, respectively. Evidently, a critical leptin level is needed to maintain menstruation. In affluent populations eating disorders are likely to be a major cause of a low leptin synthesis.